HPLC Determination of Ascorbic Acid and Dehydroascorbic Acid in Chinese Jujube - Yan-Ru, G.; Zhi-Hui, Z.; Meng-Jun, L. (Asian Journal of Chemistry, 2011)
A high-performance liquid chromatographic method for determination of ascorbic acid and dehydroascorbic acid in Chinese jujube was developed. The dehydroascorbic acid content in sample can be calculated by the difference between the total ascorbic acid (after dehydroascorbic acid reduction) and the ascorbic acid concentrations (before reduction). The method resulted linear up to 42 mg/L with precision of 1.09 % and mean recovery of 103.4 %. The least limit of detection and quantitation were 0.02 and 0.11 mg/L, respectively. The 0.1 % H3PO4 solution was opted as extracting solvent after analyzing the effect of pH on the efficiency of ascorbic acid extraction. Using of HPLC method, the ascorbic acid and dehydroascorbic acid contents in fruits of six cultivars of Chinese jujube were analyzed. The contents of ascorbic acid and dehydroascorbic acid varied from 225.10 to 424.74 mg/100g and 27.03 to 103.62 mg/ 100g, respectively, which revealed that fruits of Chinese jujube were good sources of both ascorbic acid and dehydroascorbic acid.